Purposeful Management and the Public Good: Relationships, Tensions, and Consequences - Markman, Gideon D.; Wickert, Christopher; Potočnik, Kristina; Leroy, Hannes; Muzio, Daniel; Dalpiaz, Elena (Journal of Management Studies, 2025)
Abstract Traditional management practices have long prioritized organizational performance and financial growth, primarily serving shareholder interests. However, escalating societal and environmental challenges – such as climate change, human rights violations, the dismantling of democratic institutions, and public health crises – raise questions about the adequacy of these priorities and call for greater attention to management’s role in advancing the public good. This Special Issue examines the relationships, tensions, and consequences associated with efforts to repurpose management towards broader societal aims. We distinguish between organizational purpose – the stated aspirational goals of firms – and repurposed management, which reflects broader shifts in managerial logic, practices, and institutional expectations aimed at serving the public good. The contributing articles explore how such repurposing is constructed and enacted across institutional settings, and how managerial practices influence governance structures, stakeholder dynamics, and field‐level norms to shape public outcomes – both intended and unintended. By shifting the analytical lens from purpose as internal intent to purpose as institutionally mediated consequence, we invite more inquiry into how, when, and for whom purposeful management contributes to the public good – foregrounding the institutional mechanisms, stakeholder dynamics, and societal outcomes through which purpose is interpreted, negotiated and enacted.